EXPERIMENTAL EVALUATION OF A THERAPEUTIC-PROPHYLACTIC COMPLEX ON BIOCHEMICAL MARKERS IN RAT GINGIVAL HOMOGENATES UNDER MODELLED FLUOROSIS AND ORTHODONTIC INTERVENTION - Shnaider, D.S.; Dienga, A.E.; Gorokhivskiy, V.N.; Zheliznyak, N.A.; Tsushko, I.O.; Džupa, P.; Goncharuk, S.V. (World of Medicine and Biology, 2025)
The study was devoted to evaluate the effect of a therapeutic-prophylactic complex on inflammatory and oxidative-stress biomarkers in gingival homogenates of rats exposed to chronic excessive fluoride intake and orthodontic tooth movement. Experimental studies were carried out on 40 male Wistar rats (herd breeding), 4 months of age, with an average body mass of 280±14 g. Summarising the biochemical findings, orthodontic ligature fixation superimposed on fluorosis markedly disrupted the antioxidant-prooxidant balance and intensified inflammatory processes in the gingival tissues. Administration of the therapeutic-prophylactic complex under conditions of experimental fluorosis and orthodontic intervention improved antioxidant status, decreased lipid peroxidation, and attenuated inflammation, thereby confirming the antioxidant and anti-inflammatory properties of the agents incorporated into the developed therapeutic-prophylactic complex.